Psychiatric Co-Morbidities among Elderly Individuals: A Comparative Study of Unmarried, Divorced, and Separated Status - Kelkar, Amol (Journal of Biomedical and Pharmaceutical Research, 2021)
Background: The prevalence of psychiatric disorders such as depression and anxiety is a growing concern among elderly individuals. This study examines the impact of marital status on psychiatric co- morbidities in elderly patients who are unmarried, divorced, or separated. Objective: To investigate the prevalence and severity of psychiatric disorders in elderly individuals based on their marital status. Material and Methods: A cross-sectional study was conducted in the Department of Psychiatry at a tertiary care hospital, including 60 patients aged 65 and above, who were unmarried, divorced, or separated. Psychiatric disorders were assessed using the Geriatric Depression Scale (GDS) and the Generalized Anxiety Disorder Scale (GAD-7). Results: Unmarried elders exhibited the highest prevalence of depression (60%) and anxiety (45%). The severity of psychiatric symptoms was also greatest in this group, with average depression and anxiety scores of 12.5 and 8.3, respectively. Divorced and separated individuals had lower rates and severity of psychiatric disorders. Conclusion: Marital status significantly impacts psychiatric health in elderly individuals, with unmarried elders showing the most severe psychiatric issues. Targeted interventions to improve social support and mental health care are essential for this population. Keywords: Elderly, Psychiatric disorders, Depression, Anxiety, Marital status, Social support